Legal Uncertainty of a Service as an Object of Civil Rights - O. R. Shyshka (Law and Safety)
Based on a systematic analysis of civil law norms, the problem of regulatory consolidation of a service as an object of civil rights is revealed. In particular, grammatical awareness of the content of certain norms contained in the Civil Code of Ukraine allowed us to make a rather contradictory conclusion that the service is a material good, a thing that consists in the action or activity of the service contractor. This legal paradox exists due to several shortcomings of legislative technique. The first one concerns the conjunction "including", which, according to grammar rules, refers a service (as a specific concept) as things (as a generic concept). It follows from the above that the Union "Including" should be removed in Part 1 of the Art. 177 of the Civil Code of Ukraine. The second disadvantage is due to the lack of a separate norm that would determine a clear place of the service in the system of objects of civil rights. In this regard, and taking into account the essence of the service as an object of the intangible world, it is offered to supplement Chapter 15 "intangible benefits" with a separate Article entitled "Services", which should contain a definition of the concept of this object of civil rights along with other important provisions. Moreover, the concept of a service is applied contrary to its legislative definition according to the analysis of judicial practice, namely as its result, and not as a benefit, we offer that the word "services" and the phrase "results of work" in Part 1 of the Art. 177 of the Civil Code of Ukraine should be swapped.  These amendments will contribute to legal certainty and reduce the manifestations of arbitrary interference by state agencies, including the court, in the rights protected in the Constitution of Ukraine and in the Convention for the Protection of Human Rights and Fundamental Freedoms.